Nutritional Status and Psycological Resilience in Middle Adolescent of MAN Bangkalan - Tera; Arief, Ria Qadariah; Widayanti, Linda Prasetyaning (International Conference on Sustainable Health Promotion, 2025)
The aim of this study was to describe the body mass index (BMI), resilience, self-development, and nutritional health of adolescents at MAN bangkalan. Adolescence is a period of tremendous physical growth and resilience, making teenagers susceptible to nutritional issues and psychological challenges. This study used a descriptive quantitative design with 55 respondents selected through purposive sampling. Data were collected using a modified Connor-Davidson Resilience Questionnaire and anthropometric measurements (height and weight). The data were analyzed using descriptive statistics such as mean, standard deviation, frequency distribution, and percentage. The findings showed that although most respondents had a normal BMI 52.7%, a considerable proportion were underweight 63.6% and demonstrated suboptimal levels of psychological development. The study concluded that adolescents at MAN bangkalan required optimization of both nutritional status and resilience to better support their learning processes during this developmental stage. Integrated interventions are needed, including mental health promotion, resilience building, nutrition education, and consistent support from both family and school.